Organizacija in spletne predstavitve zimskih šol v naravi v Podravski statistični regiji - Zobec, Tomaž (Šport (Ljubljana), 2019)
The purpose of this study was to analyze information about organization of the implemented winter schools in nature among primary schools in Podravska region and the quality of their web presentations. We included all of the 78 primary schools from Podravska region in our research and analyzed 53 schools (67.9 %), which had information about their winter schools in nature presented on their web sites. We searched for information about participated grades, duration, places they went, sport and other activities. We also checked if web presentation included pictures, useful information for parents, author and date of publication. Web presentations were evaluated on three level quality scale (not appropriate, good and excellent). We found out that winter schools in nature were evenly distributed between 5th, 6th and 7th grades. Most winter schools in nature lasted five days and alpine skiing was leading sport activity. The majority of schools web presentations were evaluated by score "good presentation". We also found out that the quality of web presentation was correlated with school's size and their location. Research was based on one region in Republic of Slovenia, but offers a model for monitoring of realization of different school activities. Schools in different Slovenian regions have different conditions for organization of winter schools in nature therefore we suggest that the realization of winter school in nature should be analyzed for all regions in Slovenia. The schools should be encouraged to present their activities to public in more informative and interesting way.
Keywords: alpine skiing; alpsko smučanje; osnovne šole; physical education; primary school; spletna predstavitev; sport; sports education; šola v naravi; šport; športna vzgoja; web presentation; winter school in nature; zimska šola v naravi